The application YAG:Ce3+@SiO2 phosphor for improving color deviation of phosphor-converted light-emitting diode - Thanh Binh Ly; Phan Xuan Le (Institute of Advanced Engineering and Science, 2022)
The yellow phosphor Y3Al5O12:Ce3+ (YAG:Ce3+), which sees its most popular use in white light-emitting diode (wLEDs), possess an optical spectrum that lacks the red element. The following article will propose a fresh solution for this problem, which involves adjusting the properties of Ce3+ spectrum by using exterior dye particles of ATTO-Rho101, possessing dramatic, wide absorption within the zone of green-yellow spectrum of Ce3+ emission and significant release of the red element. The globular YAG:Ce3+, which is micrometer and nanometer in size with significant dispersion (micro/nano-YAG:Ce3+) was created by employing an altered solvothermal technique. The YAG:Ce3+ produced by said technique, along with the heated micro-YAG:Ce3+ and commercial phosphors, were exteriorly covered with SiO2 and immersed in dye at the same time. Effective radiant transmission/reabsorption from Ce3+ within the YAG’s internal bowel to the dye particles of the exterior hull of SiO2, regardless of the phosphors’ size, was displayed in the YAG: Ce3+@SiO2+ dye powder amassed over the stimulation of the light of blue, which boosted the red element of it. The fluorescent microscope was considered an effective device intended for detecting the reabsorption event in grinded substances.